Low-efficiency long gamma-ray bursts: a case study with AT2020blt. Issue 1 (8th March 2022) - Sarin, N; Hamburg, R; Burns, E; Ashton, G; Lasky, P D; Lamb, G P
ABSTRACT: The Zwicky Transient Facility recently announced the detection of an optical transient AT2020blt at redshift z = 2.9, consistent with the afterglow of an on-axis gamma-ray burst. However, no prompt emission was observed. We analyse AT2020blt with detailed models, showing the data are best explained as the afterglow of an on-axis long gamma-ray burst, ruling out other hypotheses such as a cocoon and a low-Lorentz factor jet. We search Fermi data for prompt emission, setting deeper upper limits on the prompt emission than in the original detection paper. Together with KONUS- Wind observations, we show that the gamma-ray efficiency of AT2020blt is 0.3\!-\!4.5 per cent . We speculate that AT2020blt and AT2021any belong to the low-efficiency tail of long gamma-ray burst distributions that are beginning to be readily observed due to the capabilities of new observatories like the Zwicky Transient Facility.